Studi Kelayakan Bisnis dalam Usaha Jasa Pijat Profesional untuk Penyandang Tunanetra - Wasthy Novantri; Kriswanto Widiawan (Jurnal Titra, 2018)
This research was conducted to find out how the business feasibility level of professional massage services business for the blind. A suitable competing strategy for designing a new business can be done with Business Model Canvas. The business feasibility level is analyzed from the market, social, technical, and financial aspects. Data collection techniques for market analysis were conducted by interviewing 38 respondents and supported by social aspects to describe the perception of the common people towards masseuse blind. Technical analysis shows the location of the business, and the management of the company. This business requires an initial investment of Rp 122,434,500.00, has a 1.2 year payback period that is smaller than the target economic life for 5 years.